The link between stigmatization, mental health, disability, and quality of life - Amelia Rizzo; Lorena Calandi; Monica Faranda; Maria Grazia Rosano; Enrica Vinci (Advances in Medicine, Psychology, and Public Health)
This article explores the intricate relationship between stigmatization, mental health disability, and quality of life. Mental health disabilities, including conditions such as depression, anxiety, and schizophrenia, significantly impact individuals' daily functioning and overall well-being. Stigmatization, in its public, self, and structural forms, exacerbates these conditions, leading to social exclusion, reduced self-esteem, and limited access to essential resources. The article discusses how stigmatization negatively affects mental health and quality of life, creating a vicious cycle that perpetuates disability and suffering. Comprehensive interventions, including public education, cognitive-behavioral therapy, peer support, and policy changes, are necessary to dismantle structural barriers and reduce stigma. By fostering understanding and empathy, improving resource access, and integrating mental health care into primary health settings, we can enhance the quality of life and social integration for individuals with mental health disabilities.